The politics of memory in postwar Europe - Lebow, Richard Ned; Kansteiner, Wulf; Fogu, Claudio, 1963- (E-Duke books scholarly collection., 2006)
Comparative case studies of how memories of World War II have been constructed and revised in France, Germany, Austria, Switzerland, Poland, Italy, and the USSR (Russia).